Challenges in Managing Malnutrition in a Geriatric Patient: A Case Study - bin Usoh@Yusoff, Ahmad Huzaifah; binti Nordin, Nurul Izzah; bin Ismail, Nazrul Hadi; Abdul Rahman, Muhammad Ariff (Jurnal Gizi dan Pangan, 2025)
This case study aims to report on the nutrition management of low appetite in elderly due to age factor and underlying medical conditions. Mr. A, a 71-year-old Malay gentleman was referred to a dietitian at the medical ward with a diagnosis of hyperleukocytosis with Mean Corpuscular Hemoglobin Concentration (MCHC) anemia and hypercalcemia with underlying Diabetes Mellitus (DM), hypertension, and Chronic Kidney Disease (CKD) 3A. His weight and height were 59.5 kg and 159 cm, with a Body Mass Index (BMI) of 23.5 kg/m2. He claimed has lost 10 kg within 5 months. Biochemical data showed low albumin, hemoglobin, and magnesium. Intake was 69% adequacy for 24 hours of diet recall in the hospital. As for nutrition diagnosis, inadequate protein-energy intake related to decreased ability to consume sufficient energy due to lethargy as evidenced by loss of appetite and total energy intake (1,244 kcal) and protein (51.8 g) lower than recommendation (energy: 1,606 kcal, protein: 59.5‒71.4 g) were reported. The nutritional intervention aimed to encourage orally as tolerated, giving oral nutrition supplements, a palatable diet, and increasing the energy and protein intake by cutting the food into smaller pieces. As the progress of the intervention, patient’s calorie intake was increased up to 99% of the requirement. His weight on the second follow-up was 62.2 kg, increased by 2.7 kg in 10 days. However, the protein intake was still low, and the intervention was to add protein modular. As conclusion, malnutrition is common among the elderly due to decreased ability to consume sufficient energy and protein due to aging factors.